1967
DOI: 10.1021/ja00989a054
|View full text |Cite
|
Sign up to set email alerts
|

Opening the B10H102-cage to produce B10H12(Et2S)2

Abstract: Work on recovery of the (NH4)2B10H~0 from the double salt by use of other solvents is in progress. With large excesses of HC1 the reaction gives some free NH4C1 and correspondingly higher quantities of B10H12-(Et2S)2. Several samples have been allowed to react with propargyl bromide, and the expected bromomethylcarborane derivative was ~b t a i n e d .~Muetterties has reported obtaining a bridge-hydrogen structure from the BloHlo2-i o n 6 Dehydration of an aqueous solution of (H30)2B10H10 gave a white solid fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
1
12
0
Order By: Relevance
“…[9] Now we have found that trans-M 2 [B 20 H 18 H 19 ] À ion, which is designated as fac-[B 20 H 19 ] À in the following discussion. It is known that under acidic conditions the closo-[B 10 H 10 ] 2À ion reacts to form nido-B 10 H 13 X, [25,26] nido-B 10 H 12 X 2 , [27,28] or BF 3 /[BF 4 ] À . [29][30][31] In view of these reactions, the rearrangement of trans-[B 20 H 18 ] 2À (Figure 1) might be initiated by protonation of one of its two {B 10 (Figure 1).…”
mentioning
confidence: 99%
“…[9] Now we have found that trans-M 2 [B 20 H 18 H 19 ] À ion, which is designated as fac-[B 20 H 19 ] À in the following discussion. It is known that under acidic conditions the closo-[B 10 H 10 ] 2À ion reacts to form nido-B 10 H 13 X, [25,26] nido-B 10 H 12 X 2 , [27,28] or BF 3 /[BF 4 ] À . [29][30][31] In view of these reactions, the rearrangement of trans-[B 20 H 18 ] 2À (Figure 1) might be initiated by protonation of one of its two {B 10 (Figure 1).…”
mentioning
confidence: 99%
“…An alternative method is to start from commercially available B 10 H 10 (Et 4 N) 2 , which is cheap, stable, and nontoxic. It can be readily converted to the precursor B 10 H 12 (Et 2 S) 2 , which is reactive, but easy to handle and suitable for synthesis of o ‐carborane–pyridine derivatives by reaction with pyridine‐bearing alkynes (Scheme ) . On the basis of this modified synthetic approach, three new o ‐carborane‐functionalized HtrueCN^ ligands ( a – c in Figure and Scheme ) were prepared in high yields and with low costs.…”
Section: Resultsmentioning
confidence: 99%
“…The reverse conversion requires the opening of the very stable [B 10 H 10 ] 2À cage. In strong acidic medium and in the presence of chelating and not highly polar solvent L, the cage [B 10 H 10 ] 2À is opened and 6,9-L 2 B 10 H 12 is produced [11][12][13]. When the solvent L is non polar and not chelating as C 6 H 6 and in presence of the very strong acid CF 3 SO 3 H, the conversion products are 6-(C 6 H 5 )B 10 H 13 and 6-(OSO 3 H)B 10 H 13 [13].…”
mentioning
confidence: 99%
“…The mechanism of the reaction between [B 10 H 10 ] 2À and concentrated acids would be very similar to that between strong acid and a [B 10 H 10 ] 2À anion salt in diethylsulphide suspension, from which (Et 2 S) 2 B 10 H 12 is obtained [12,13]; the first step is the fixation of one proton on each of the apical positions. Cage opening occurs when hydrogen-bridge bonds form between (B-5 and B-6), (B-8 and B-9) and boron-boron bonds are destroyed (Fig.…”
mentioning
confidence: 99%